2019
DOI: 10.3233/jad-190401
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Alzheimer-Associated Neuronal Thread Protein is not Elevated in Patients with Subjective Cognitive Decline and Patients with Depressive State

Abstract: Subjective cognitive decline (SCD) is a risk factor for Alzheimer's disease (AD). Urinary Alzheimer-associated neuronal thread protein (AD7c-NTP) has been identified as a biomarker for AD. It was hypothesized that if urinary AD7c-NTP were also elevated in SCD, as it is in prodromal AD (mild cognitive impairment stage), it could be a convenient and efficient clinical biomarker for the early diagnosis of SCD. SCD is often accompanied by a depressive state (DS), and the impact of DS on urinary AD7c-NTP levels rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…In the present study, it was revealed that the levels of urinary AD7c-NTP were not higher in SCD patients compared with the NC group. This result is consistent with previous results from our research group [15]. The reason for these results may be that SCD is still a very early stage of the disease when neuropsychological test scores are normal; thus, tau protein may not be increased or detected at this stage [41].…”
Section: The Relationship Between Urinary Ad7c-ntp Levelssupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, it was revealed that the levels of urinary AD7c-NTP were not higher in SCD patients compared with the NC group. This result is consistent with previous results from our research group [15]. The reason for these results may be that SCD is still a very early stage of the disease when neuropsychological test scores are normal; thus, tau protein may not be increased or detected at this stage [41].…”
Section: The Relationship Between Urinary Ad7c-ntp Levelssupporting
confidence: 93%
“…In addition, a previous study reported that urinary AD7c-NTP is elevated in late-life depression with cognitive impairment [13]. Furthermore, existing research recognizes that urinary AD7c-NTP has a critical role in cognitive decline, but not in depression or other diseases [12][13][14][15]. Urinary AD7c-NTP testing is noninvasive, radiation-free, repeatable, and easy to carry out.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urine AD7c-NTP was increased in MCI and AD (Youn et al, 2011;Ma et al, 2015). However, AD7c-NTP was not elevated in patients with SCD (Li et al, 2019). While there have been considerable advancements in the field, the lack of changes on the above-mentioned markers in the preclinical stage of AD poses significant challenges for the use of such biomarkers in the clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…In a pilot study, a targeted and quantitative metabolomics approach is applied, and several panels composed of urinary metabolites are identified to distinguish MCI and AD from cognitively healthy controls with high sensitivity and specificity [102]. Several novel urinary biomarkers for the early diagnosis of AD have been discovered, and some of them are Alzheimer-associated neuronal thread protein (AD7c-NTP) [103][104][105][106], monocyte chemoattractant protein-1 (MCP-1) [107], and dysregulated arginine metabolism [108].…”
Section: Biomarkers In the Urine And Salivamentioning
confidence: 99%